The perils of debt deflation in the euro area: A multi regime model - Willi Semmler; Alexander Haider (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Academic research and policy makers in the Euro area are currently concerned with the threat of debt deflation and secular stagnation in Europe. Empirical evidence seems to suggest that secular stagnation and debt deflation in the Euro area may be rather slowly developing. Yet what appears as major peril is that debt deflation with a lack of economic growth, rising real interest rates and further rising debt may trigger household defaults, defaults of firms and banks, rise of risk premia, and default risk of certain sectors of the economy or sovereign defaults. It is this rising default and financial risk then that may lead to a regime change to a slowly moving debt crisis with high financial risk and high financial stress. In order to explore those issues, a macro policy model of Svensson type is introduced, exhibiting a regime of low and high financial stress. Then, a four dimensional multi-regime VAR is employed to an Euro area data set to support the theoretical model and the claim that in particular Southern Euro area countries are affected by debt deflation and financial market stress.
urn:nbn:de:bsz:180-madoc-401268
Keywords: E43; F36; F45; 330; Debt Deflation; Secular Stagnation; Euro Area; Interest Rate Spread; Multi Regime Model